2018
DOI: 10.1080/19942060.2018.1479662
|View full text |Cite
|
Sign up to set email alerts
|

Flow-induced vibration of a radial gate at various opening heights

Abstract: This study proposes a method for mitigating the flow-induced vibration of a radial sluice gate to ensure operational safety and long-term stability. To this end, a supplementary plate was attached to the lower rear surface of the gate and its effect on vibration reduction is investigated using a fluid-structure interaction (FSI) analysis. Specifically, a three-dimensional finite-element method (FEM) model of the gate partially submerged in water was constructed and then validated by comparing the numerical res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…It is caused by the split and reattachment of the flow of water around the radial gate and by the resulting unstable flow under the gate [42,43]. Radial gates of the Japanese Wachi Dam and the US Folsom Dam were destroyed due to vortex-induced vibrations generated by the partially opened gates in 1967 and 1995, respectively [44].…”
Section: Analysis Results and Discussion Of Vibration Effectmentioning
confidence: 99%
“…It is caused by the split and reattachment of the flow of water around the radial gate and by the resulting unstable flow under the gate [42,43]. Radial gates of the Japanese Wachi Dam and the US Folsom Dam were destroyed due to vortex-induced vibrations generated by the partially opened gates in 1967 and 1995, respectively [44].…”
Section: Analysis Results and Discussion Of Vibration Effectmentioning
confidence: 99%
“…Markovic et al [24] came up with a measure to effectively suppress hydrodynamic loads through placing a penetrating orifice at the gate bottom. Lee et al [25] modified the shape of the curved gate bottom and added a guide plate to stabilize the flow. When the gate opening height is 0.08 m, the vibration reduction can reach 75%.…”
Section: Flow Field Distributionmentioning
confidence: 99%
“…To date, many scholars have investigated the fluid-induced vibration (FIV) of SRGs through prototype tests [3], numerical structural calculations [4,5], hydroelastic modeling experiments [6], and principle analyses [7,8]. The analyses showed that the supporting arms were the weakest component of the SRG, which could finally lead to the failure of the gate.…”
Section: Introductionmentioning
confidence: 99%